2018
DOI: 10.1073/pnas.1719355115
|View full text |Cite
|
Sign up to set email alerts
|

Macrocycle ring deformation as the secondary design principle for light-harvesting complexes

Abstract: Natural light-harvesting is performed by pigment-protein complexes, which collect and funnel the solar energy at the start of photosynthesis. The identity and arrangement of pigments largely define the absorption spectrum of the antenna complex, which is further regulated by a palette of structural factors. Small alterations are induced by pigment-protein interactions. In light-harvesting systems 2 and 3 from , the pigments are arranged identically, yet the former has an absorption peak at 850 nm that is blue-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 56 publications
3
27
2
Order By: Relevance
“…The obtained results, reported in Table S5 of the ESI, † clearly show that, if we use the crystal structures without any relaxation, a very large (and unphysical) blue-shi of ca. 2000 cm À1 is found for both a and bBChls when moving from LHL to LL, exactly as found by De Vico et al 20 However, as soon as we relax the bond lengths (and bond angles), still keeping the dihedral angles frozen (and hence the macrocycle curvature), these differences almost disappear: they reduce to 40 cm À1 and 60 cm À1 when calculated for the isolated a and bBChls, respectively, and to 65 and 186 cm À1 when the effect of the MMPol environment is included. If we further relax all the internal degrees of freedom together with the close by residues, we do not see any further signicant change, showing that the bond lengths play a major role in determining the excitation energy.…”
Section: Dissecting the Possible Origins Of The Spectral Differencessupporting
confidence: 90%
See 3 more Smart Citations
“…The obtained results, reported in Table S5 of the ESI, † clearly show that, if we use the crystal structures without any relaxation, a very large (and unphysical) blue-shi of ca. 2000 cm À1 is found for both a and bBChls when moving from LHL to LL, exactly as found by De Vico et al 20 However, as soon as we relax the bond lengths (and bond angles), still keeping the dihedral angles frozen (and hence the macrocycle curvature), these differences almost disappear: they reduce to 40 cm À1 and 60 cm À1 when calculated for the isolated a and bBChls, respectively, and to 65 and 186 cm À1 when the effect of the MMPol environment is included. If we further relax all the internal degrees of freedom together with the close by residues, we do not see any further signicant change, showing that the bond lengths play a major role in determining the excitation energy.…”
Section: Dissecting the Possible Origins Of The Spectral Differencessupporting
confidence: 90%
“…3, but now the simulated spectra of LL-LH2 and HM-PucD have been obtained by correcting the site energies by the additional blue-shi induced by the different out-of-plane distorsion of aBChl and bBChl as predicted by crystal data (for HM-PucD we have assumed the same distorsion as LL-LH2). This conclusion in some way goes against what reported in recent computational studies by De Vico and coworkers, 20,58 who used a multistate multiconguration restricted active space with second-order perturbation theory correction (MS-RASPT2) to calculate the excitation energies of the BChl at their crystal structure. In the same study, instead, a different source of the blue shi was suggested, that is, the change in the BChl macrocycle ring curvature.…”
Section: Dissecting the Possible Origins Of The Spectral Differencescontrasting
confidence: 56%
See 2 more Smart Citations
“…As a matter of fact, more accurate QM methods have been also used for LH complexes, mostly as benchmarks for less expensive methods [41,42], even though some direct applications have also been presented. In particular, we quote here the complete active space methods in combination with perturbation theory (CAS-PT2) used for bacteriochlorophylls and carotenoids of LH2 [43,44], the approximate second-order coupled cluster (CC2) and the algebraic diagrammatic construction through second-order (ADC(2)) methods used for dimers and larger clusters of (bacterio)chlorophylls [45,46], and the Bethe-Salpeter equation and the GW approximation (BSE/GW) used for phycoerythrobilins of PE545 [47].…”
Section: The Excitonic Hamiltonianmentioning
confidence: 99%